The common solution for a generalized equilibrium problem, a variational inequality problem and a hierarchical fixed point problem - Karahan, Ibrahim; Secer, Aydin; Ozdemir, Murat; Bayram, Mustafa (SPRINGEROPEN, 2015)
The present paper aims to deal with a new iterative method to find a common solution of a generalized equilibrium problem, a variational inequality problem and a hierarchical fixed point problem for a sequence of nearly nonexpansive mappings. It is proved that the proposed method converges strongly to a common solution of above problems under some assumptions. The results here improve and extend some recent corresponding results by many other authors.
Keywords: generalized equilibrium problem; variational inequality; hierarchical fixed point; projection method; nearly nonexpansive mappings; STRONG-CONVERGENCE; ITERATIVE METHODS; NONEXPANSIVE-MAPPINGS; VISCOSITY METHOD; SYSTEMS; Mathematics